Differences in biological traits composition of benthic assemblages between unimpacted habitats. (May 2017) - Bolam, S.G.; Garcia, C.; Eggleton, J.; Kenny, A.J.; Buhl-Mortensen, L.; Gonzalez-Mirelis, G.; van Kooten, T.; Dinesen, G.; Hansen, J.; Hiddink, J.G.; Sciberras, M.; Smith, C.; et al.
Abstract: There is an implicit requirement under contemporary policy drivers to understand the characteristics of benthic communities under anthropogenically-unimpacted scenarios. We used a trait-based approach on a large dataset from across the European shelf to determine how functional characteristics of unimpacted benthic assemblages vary between different sedimentary habitats. Assemblages in deep, muddy environments unaffected by anthropogenic disturbance show increased proportions of downward conveyors and surface deposit-feeders, while burrowing, diffusive mixing, scavenging and predation traits assume greater numerical proportions in shallower habitats. Deep, coarser sediments are numerically more dominated by sessile, upward conveyors and suspension feeders. In contrast, unimpacted assemblages of coarse sediments in shallower regions are proportionally dominated by the diffusive mixers, burrowers, scavengers and predators. Finally, assemblages of gravelly sediments exhibit a relatively greater numerical dominance of non-bioturbators and asexual reproducers. These findings may be used to form the basis of ranking habitats along a functional sensitivity gradient. Highlights: A trait-based approach is used to determine how functional characteristics of unimpacted assemblages vary between habitats. Assemblages in deep, muddy environments show increased proportions of downward conveyors and surface deposit-feeders. Deep, coarser sediments are numerically more dominated by sessile, upward conveyors and suspension feeders. Coarse sediments in shallower regions are dominated by the diffusive mixers, burrowers, scavengers and predators. These findings may be used to form the basis of ranking habitats along a functional sensitivity gradient.